2006
DOI: 10.2353/ajpath.2006.060161
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblastic Oxidative Stress and the Release of Cell-Free Feto-Placental DNA

Abstract: Considerable quantities of cell-free fetal DNA circulate in the maternal blood during human pregnancy, but the origin of the DNA remains uncertain. Circumstantial evidence suggests the placenta is the principal source, so we tested the hypothesis that release occurs from the syncytiotrophoblast after the induction of apoptotic changes. Villous explants from normal placentas delivered by elective caesarean section were cultured under normoxic conditions (10% oxygen) for up to 20 hours or exposed to hypoxia (0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 21 publications
4
149
1
7
Order By: Relevance
“…Previously, it has been demonstrated that there was no correlation between the concentration of maternal plasma fetal DNA and placental size during the first trimester (Wataganara et al, 2005). While the amount of fetal DNA released into maternal plasma is determined by placental apoptosis (Tjoa et al, 2006), circulating RNA concentration is additionally influenced by the relative placental tissue expression of a gene (Ng et al, 2003a,b). Therefore, this prompted us to study fetal growth by targeting RNA transcripts that are related to growth or IUGR pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that there was no correlation between the concentration of maternal plasma fetal DNA and placental size during the first trimester (Wataganara et al, 2005). While the amount of fetal DNA released into maternal plasma is determined by placental apoptosis (Tjoa et al, 2006), circulating RNA concentration is additionally influenced by the relative placental tissue expression of a gene (Ng et al, 2003a,b). Therefore, this prompted us to study fetal growth by targeting RNA transcripts that are related to growth or IUGR pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Sumado a esta evidencia, otro estudio 37 mostró que los niveles de ffDNA se correlacionaron con la alteración de la perfusión placentaria (i.e., aumento del índice de pulsaciones en la arteria uterina) y la severidad de la enfermedad. Estos resultados refuerzan el concepto de que el daño placentario seria el origen del ffDNA en la circulación materna, y es posible que estos niveles permitan la identificación del grupo de embarazadas pre-eclámpticas con mayor riesgo perinatal 38 . En ese sentido, Illanes y cols.…”
Section: Niveles De Adn Libre De Origen Fetal (Ffdna)unclassified
“…It is known from in vitro studies that hypoxia induces both apoptosis and necrosis in villous explants of the placenta, with an accompanying release of cellfree DNA. This link between the release of cell-free DNA and hypoxia led to the suggestion that release of cell-free DNA may be a useful biomarker of placental well-being during pregnancy (Tjoa et al, 2006). Although it is accepted that the placenta is the main source of cff DNA, it has yet to be established by experiment which placental cells are the main contributors to the cff DNA in the maternal circulation.…”
Section: Origins Of Cell-free Plasma Dna and Identifying Biomarker Dmentioning
confidence: 99%